Elemental and isotopic composition of nitrogen, oxygen, and argon in Allan Hills ice cores ... - Bender, Michael; Higgins, John; Yan, Yuzhen (U.S. Antarctic Program (USAP) Data Center, 2019)
This file includes the d15N, O2/N2 ratio, Ar/N2 ratio, and d18O of O2 (d18Oatm) in Allan Hills ice cores (ALHIC1502 and ALHIC1503). ...